A intercambialidade modo-temporal : análise sociolinguística da alternância de tempo e modo verbal na fala dos moradores de Vitória - Barbosa, Astrid Franco (2011)
This work, based on Variationist Sociolinguistics theoretical perspective, studies three types of alternation in the speech of inhabitants of Vitoria (ES): i) mode alternation; ii) time and mode alternation; iii) time alternation. Among the three types of alternation presented here, we studied more specifically the first one, the mode alternation, by the way, that is the alternation between subjunctive and indicative forms. We tried to understand which factors can influence the use of the indicative form instead of the subjunctive form, besides to verify in which context this alternation occurs more frequently.Three linguistic variables and one social were identified, by the program GOLDVARB that we have used to analyze the data, as the most significant in terms of probability which are: the matrix verb, assertiveness, verb tense of matrix sentence, and education level. In order to check the alignment of Vitoria in the alternation of indicative and subjunctive forms, we compared our results to those found by Rocha (1997), from Rio de Janeiro/Brasília; Carvalho (2007), from Cariri; and Oliveira (2007), from João Pessoa. With respect to the alternation of time and mode, indicative present x subjunctive future, it is necessary to deepen the analysis working as a much more restricted groups of factors, what should be done later. There was a selected linguistic variable, type of sentence, as the most statistically relevant. And the last alternation is of mode between imperfect subjunctive x subjunctive future that doesn´t occur on the main clause, as we thought, but in the complement clause. We will keep on this analysis in a future study.